The diversity of macromoths (lepidoptera : heterocera) in the lowland forest at aboretum of Universiti Malaysia Sarawak (Unimas) - Erica Hadari, Anak Bertha (University Malaysia Sarawak (UNIMAS), 2013)
The study aimed to determine the diversity of the macromoths in the lowland forest at Aboretum, UNIMAS, Kota Samarahan, Sarawak. Modified Pennsylvania light traps with 160 W mercury vapor was used to attract the macromoths in both ground (1m) and canopy (21m) level of the lowland forest. A total of 348 individuals comprising 99 species from 13 families and 12 subfamilies were recorded in twelve nights of sampling. The macromoths’ diversity was considerably low with a Shannon’s’ Diversity Index, 4.161 and Simpson Index of 0.9769. The canopy level shows lower diversity compared to the ground level. Results show that large numbers of species occupying the ground level compared to the canopy level. The pattern of vertical distribution varied according to certain families. Geometridae was the highest family recorded.